Thursday
March 23, 2017

Post a New Question

Posted by on Sunday, December 4, 2011 at 9:54pm.

Write the partial fraction decomposition of the rational expression.
6x^2+1/x^2(x-1)^2

  • precalc - , Sunday, December 4, 2011 at 10:39pm

    Because of the duplication of factors we could have

    A/x + B/x^2 + C/(x-1) + D/(x-1)^2 = (6x^2 + 1)/(x^2(x-1)^2)
    multiply by x^2(x-1)^1
    A(x-1)^2 + Bx(x-1)^2 + Cx^2(x-1) + Dx^2 = 6x^2 + 1
    let x=0 --> A = 1
    let x=1 --> D = 7

    then (x-1)^2 + Bx(x-1)^2 + Cx^2(x-1) + 7x^2 = 6x^2 + 1
    let x=2 --> 1 + 2B + 4C + 28 = 24+1
    or B + 2C = -2 (#1)

    let x = -1 --> 4 - 4B - 2C + 7 = 7
    or 2B + C = 2 (#2)

    2 (#1) - #2
    3C = -6
    C = -2
    then B = 2 form #1

    so (6x^2 + 1)/(x^2(x-1)^2)
    = 1/x^2 + 2/x - 2/(x-1) + 7/(x-1)^2

  • precalc - , Monday, December 5, 2011 at 11:25am

    Looks like it should have said

    A/x^2 + B/x + C/(x-1) + D/(x-1)^2 = (6x^2 + 1)/(x^2(x-1)^2)

    but the solution from there on is correct.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question